Nanocouplers for Infrared and Visible Light. (4th October 2012) - Andryieuski, A.; Lavrinenko, A. V.
Abstract : An efficient and compact coupler—a device that matches a microwaveguide and a nanowaveguide—is an essential component for practical applications of nanophotonic systems. The number of coupling approaches has been rapidly increasing in the past ten years with the help of plasmonic structures and metamaterials. In this paper we overview recent as well as common solutions for nanocoupling. More specifically we consider the physical principles of operation of the devices based on a tapered waveguide section, a direct coupler, a lens, and a scatterer and support them with a number of examples.